Schools and mass media as political socialization agents of national identity a case study of a rural public high school. - Farinas, Ferlan L.
This study was undertaken to examine the national identity of the students of San Nicolas national High School. After a careful analysis of the data gathered, the researcher came up with several conclusions. First, the curriculum used by the school has components that promote national identity. The selected teacher's pedagogy and the school's curricular and extracurricular activities also promote the various orientations and topics that reflect national identity. The overall effect of the school to the national identity of the students is positive. The year level of the students has a small positive effect on the level of their national identity, which means that the higher the year level of a student, the more likely that his/her national identity is higher. The students' exposure to mass media (i.e. television, radio and book) is low and most often to programs and texts that are less likely to promote sense of national identity. However, they are also considerably exposed to programs and texts that promote national identity such as news programs and textbooks. Overall mass media has a small negative effect on the national identity of the students. However, television and book exposure alone have positive effect to national identity. Radio exposure has greater effect on national identity but negative. The level of national identity of the students is either high or moderate.